Evidence‐Based Post‐operative Management of Chronic Rhinosinusitis. (23rd August 2013) - Lee, Jivianne T.; Han, Joseph; Hwang, Peter H.; Stringer, Scott P.
Abstract : Program Description: Endoscopic sinus surgery (ESS) without adequate post‐operative care can lead to unsatisfactory results. Judicious post‐operative management of chronic rhinosinusitis (CRS) is essential to optimize surgical outcomes. Recent years have witnessed significant expansion and innovation with respect to post‐op interventions. The purpose of this miniseminar is to evaluate and discuss the extensive complement of post‐op therapies currently available for CRS from an evidence‐based perspective. A panel of academic leading rhinologists will be conducting this miniseminar using a multimedia case‐based format with audience interactive questions. Clinical cases illustrating implementation of various post‐op regimens will be presented in addition to review of relevant evidence. Educational Objectives: 1) Evaluate current post‐op therapies for CRS and appraise their roles in maximizing surgical outcomes. 2) Assess the use of biomaterials, novel adjuvant therapies, and recent innovations in pharmaceutical delivery post‐ESS. 3) Discuss the relevant evidence and proper application of each therapeutic modality in the post‐operative setting.